Formulation Of The Application Of Restorative Justice To Offenders Of Corruption In Indonesia - Muhammad Rahjay Pelengkahu; Indirwan Indirwan (Faculty of Law, Universitas Lampung, 2022)
Today's paradigm for resolving corruption issues should move from retributive to restorative justice. The existing criminal justice system, which stresses retributive justice, is incapable of achieving the goals intended by the law's drafters, namely the suboptimal restitution of public financial losses. In light of the failure of retributive justice to prevent and remove corruption, it is vital to adopt a new strategy called restorative justice. In addition to preventing and eradicating corruption offenses, the restorative justice strategy may be utilized to maximize the recovery of losses to the state. This is a normative study with numerous primary, secondary, and tertiary legal resources serving as data sources. The evidence is then descriptively and qualitatively examined, resulting in a conclusion addressing the legal issues. The failure of retributive justice procedures based on vengeance and neoclassical theory to satisfy society's sense of justice sparked the idea of incorporating restorative justice into the concept of punishment, particularly the punishment of those who commit corruption offenses. To use restorative justice approaches to resolving corruption cases, it is essential to establish systematized and exhaustive legal processes to eradicate corruption. The state still needs to create legal processes for resolving corruption cases utilizing restorative justice approaches. In this work, the author attempts to develop a legal system for resolving corruption cases with restorative justice approaches that consider crucial variables and the repercussions of implementing this procedure.